Comparative Microstructure Characteristics of Synthesized PbS Nanocrystals and Galena - Ehab AlShamaileh; Bashar Lahlouh; Ahmed N. AL-Masri; Mariam Al-Qderat; Wadah Mahmoud; Mohammad Alrbaihat; Iessa Sabbe Moosa (Sci, 2024)
Lead sulfide (PbS) on the nanoscale was synthesized via a chemical route at room temperature using lead nitrate {Pb(NO3)2} and sodium sulfide (Na2S). The Na2S was prepared at ~105 °C using sodium hydroxide (NaOH) and sulfur (S) powder. The produced PbS, denoted as Lab-PbS, was compared with a high-concentration PbS phase of galena. The produced Na2S and Lab-PbS were examined using scanning electron microscopy and energy dispersive X-ray spectroscopy for microstructural and chemical analysis. The results confirmed a high-purity PbS compound (>99%) with a nanoscale particle size. The results showed that ultrasonic agitation was vital for obtaining the nanoparticle size of the Lab-PbS. Furthermore, thin films from the synthesized Lab-PbS and galena were successfully thermally evaporated on glass, quartz, and silicon substrates. The formation of nanometric grains was confirmed by scanning electron microscopy (SEM). XRD and FTIR spectroscopy were carried out for the Lab-PbS, galena fine powders, and galena thin films. The average crystal diameter was calculated for the galena thin films and was found to be approximately 26.6 nm. Moreover, the UV–Visible transmission curve was measured for the thin films in the wavelength range of 200–1100 nm in order to calculate the bandgap energy (Eg) for the thin films. The values of Eg were approximately 2.65 eV and 2.85 eV for the galena and Lab-PbS thin films, respectively. Finally, the sintering of the Lab-PbS and galena powders was carried out at ~700 °C for 1 h under vacuum, achieving relative densities of ~98.1% and ~99.2% for the Lab-PbS and galena, respectively.